Open Framework Allotropes of Silicon: Potential Anode Materials for Na and Li-ion Batteries. (20th July 2016) - Marzouk, Asma; Balbuena, Perla B.; El-Mellouhi, Fedwa
Abstract: We report a computational investigation of the potential of new open-framework allotropes of silicon as Na and Li-ion batteries. Most anode materials used in energy storage systems are characterized by a very high capacity but are very sensitive to the charge/discharge cycling. It is hence appealing to design a material with at the same time a good capacity and maintaining crystalline morphology upon multiple battery operation cycles. We investigated using electronic structure the capacity of a recently synthesized framework of silicon c-Si24 as an anode material and showed that the breaking of some Si-Si bonds leads to the formation of two new more flexible allotropes. We demonstrate that the major advantage of these allotropes is their reversible stable capacity that would sustain after several battery charge-discharge cycles.